Migration and the Labour Market – The Case of Poland and the Baltic States - Piekutowska, Agnieszka; Grabowiecki, Jerzy (Olsztyn Economic Journal, 2017)
This article aims to examine the economic impact of emigration on labour market developments in Poland, Lithuania, Latvia and Estonia (since EU accession) in a comparative perspective. The realization of this goal required an analysis of the literature as well as statistical analysis. The impact of emigration on the unemployment rate reduction, the issue of labour shortages and the wage effect of emigration and rising inflation were analysed. The main conclusion of the study is that the nature of these effects seems to be country-specific. The analysis indicated that along with reduction in labour supply, the unemployment rate reduction, the wage growth pressure and inflation were observed in all of the analysed countries. However, the strength of these developments varied among them. This differentiation can be attributed firstly to a different scale and intensity of emigration. Furthermore, differences among the analysed countries in the scope of wage pressure and inflation should be explained in the context of changes in the domestic workers productivity.